Étude des catégories opératives pour analyser l’activité d’enseignants - Hélène Veyrac; Julie Blanc (Recherches en Éducation)
Categorization, as a basis of the thought process, is considered to be a means for describing part of the activity. A data collection protocol called “study of operative categories” makes it accessible to activity analysis. This protocol is in line with research into the categorizations of students by teachers and complements it with a phase during which the rules of action are expressed based on the “schemes” concept. With the help of a photo gallery of their class, 67 teachers from 6 high schools demonstrate their perception of the students by arranging the photographs in groups. These groups constitute the operative categories and the teachers then explain the specific teaching practices used for each category of students. The data collection and processing protocol, illustrated by an example of how student participation is regulated in the class, makes it possible to give precise indications on the method. The results show that different teachers who designate similar categories of students do not systematically evoke the same rules of action. They also show that a teacher mobilizes multiple characteristics to describe the students in his/her class. Finally, they demonstrate a certain specialization in the way teachers view their students: one group of students is perceived based on certain characteristics which are not pertinent to another group of students. This approach complements those aiming to describe the differentiated treatment of students by teachers. Applied to other operative categories, it could enhance the field of activity analysis, particularly in terms of understanding intra-individual variability.